Ethnobotany of Syzygium polyanthum (Wight) Walp In Terengganu, Peninsular Malaysia - Nur Fatihah, Hasan Nudin; Mohammad Moneruzzaman, Khandaker; Abd Manaf, Ali (2020)
Plant with medicinal potentials has contributed significantly to the evolution of the modern health care system. Medicinal plants remain the only way forward as they are gaining more acceptability and recognition all over the world. The emergence of new diseases all over the world has necessitates the need for the exploration of plant parts for the invention of promising drugs. To achieve this, prior knowledge of the medicinal plants is needed from the traditional medicinal practitioners and any other person utilising plants for medicinal purposes. This study aims at documenting traditional knowledge of Syzygium polyanthum cultivars (Serai Kayu and Serai Kayu Hutan) in Terengganu. Three hundred and eighty four respondents were interviewed with the aid of semi structured questionnaire. The study reported Serai Kayu and Serai Kayu Hutan to be used as ulam, spices and medicinal respectively. Leaves were found to be the most utilized part and Decoction is the most prepared method. However, the study recommends immediate conservation of the plant and adoption of Malays traditional culture utilisation of the species; due to its medicinal potentials.